The Breakdown of Health-care.gov project - A Study with Specific Emphasis on Project Management Body Of Knowledge (PMBOK) - Harini Anandarao,; Ainul Aisyah Ainul Hisham,; Abdul Azim Jamalulais,; Nur Fatini Mohd Ali,; Muhammad Firas Roslan,; Mohamad Aizi Salamat, (Applied Information Technology And Computer Science, 2023)
This case study examines the disastrous launch of Healthcare.gov, initiated by US President Barack Obama as a commitment to revamp the nation's public health system. A portion of the Affordable Care Act 2013 proved a failure due to mismanagement, technical difficulties, and politics, which, as a result, caused repercussions among other projects. This study aims to identify the primary determinants of e-government project failure, encompassing inadequate integration management, time limitations, project quality concerns, ineffective resource and personnel allocation, limited participation in risk assessment and guidance, and a scarcity of managed government contracts. The examination of project failures is conducted within the framework of the Project Management Body Of Knowledge (PMBOK), which comprises the management of integration, time, risk, scope, quality, human resources, and procurement. Every incident has been analyzed and discussed to address the issue and how it impacts government project initiatives involving project stakeholders. This report analyses the Healthcare.gov incident to shed light on the project's failure and offer recommendations for enhancing the planning and execution of government technology initiatives on a large scale in the future. It underscores the significance of efficient project management and prioritising user experience.